A New Potentiomertic Sensor for a Preventing Alzheimer's Disease Drug Based on Nano-Silver Modified Carbon Paste Electrode - Rostam Shabani; Laeli Badisar; Razieh Moosavi (Iranian Journal of Health, Safety and Environment, 2021)
Due to the importance of vitamin B6 (VB6) drug for human health, especially in the treatment of Alzheimer's disease, it is useful to develop new, simple, cheap and rapid methods for the determination of this compound. A high linear range and a sensitive potentiometric sensor for VB6 based on carbon paste electrode (CPE) modified with synthesized silver nanoparticles by co-precipitation method were prepared. The sensor fully characterized in terms of distinctive nanoparticles quality, electrode composition, and usable pH range. Under optimal conditions, a linear calibration curve with range 1×10-6 to 1×10-2mol L−1 and a detection limit of 4.84×10-7molL−1 was obtained for VB6 determinations. The research introduces the design and construction of the nanocomposite modified CPE for simple and low-cost determination of VB6 in pharmaceutical formulation. Validation of the method indicates the suitability of the sensor for application in quantity control analysis of VB6 drug in pharmaceutical formulation preparations.